Metode Pengawasan Kepala Sekolah Di TK Kemala Bhayangkari Kabupaten Bone dalam Memberikan Informasi Manajemen Kelas Untuk Meningkatkan Kualitas Kinerja Guru - Agustina SPd (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This research is a school action research that aims to improve the quality of teacher performance through the supervision of the principal by providing classroom management information. The subjects of the study were all Kemala Bhayangkari Kindergarten teachers in the 2021 academic year. The action research was carried out in two cycles with 5 meetings in each cycle. Data collection techniques were Focus Group Discussion (FGD), observation and questionnaires to measure the quality of teacher performance given. at the end of each action cycle. The data collected were analyzed qualitatively and quantitatively. The results of the research analysis show that the results of the quality of teacher performance before the implementation of principal supervision through the provision of classroom management information obtained an average value of 108.3 or were in the medium category. Based on the above analysis, it can be concluded that the quality of teacher performance in Kemala Bhayangkari Kindergarten has increased after the implementation of principal supervision through the provision of classroom management information.